Graphical thinking for science and technology through knowledge visualization - Ursyn, Anna, 1955- (Advances in multimedia and interactive technologies (AMIT) book series., 2020)
"This book explores ways to integrate knowledge from various disciplines to think in a holistic way about data and information. It also examines how processes and products in nature allow us to think cross-disciplinary, use our abstract thinking skills, and re-examine our findings by graphical thinking through knowledge visualization"--